THE EFFECT OF BRAIN GYM ON THE LEVEL OF INDEPENDENCE OF THE ELDERLY - Nurcahyaningtyas, Widya; Widati, Amila; Rofiq, Muhamad Ainur (Nurse and Health: Jurnal Keperawatan, 2024)
Background: The height ratio dependence elderly in Indonesia is very worrying. The ratio dependence elderly in Indonesia are increasing from 14.02% in 2017 to 16.76% in 2021. East Java including the top 5 province with dependence elderly and occupying ranking to 3 after Central Java Province. Objectives: To know the effect of brain gym on level independence elderly. Methods: This was pre-experiment with use approach one group pre-post test design. Population in the study is all over elderly people in the village Ringinsari, District Kandat Kediri Regency. Technique of taking sample done with technique Consecutive Sampling. Data analysis was carried out through two stages. Stage First that is analyzing pre and post independence data elderly using the pre post test design test. Stage second is analyze the effect of brain gym on level independence elderly using the Wilcoxon test. Results: Research results show that there is change in level of independence before and after given Brain Gym intervention. The results of data analysis using the Wilcoxon test (level of 95% confidence interval is p= 0.000<0.05) which means there is the effect of brain gym to level independence elderly in the village Ringinsari, District Kandat Kediri Conclusion: Brain gym influential to level independence in the elderly.